1981
DOI: 10.1093/ageing/10.3.141
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Falls in the Elderly: A Community Study

Abstract: In 2793 respondents aged 65 and over in a survey of a geographically defined community, who were asked about falls in the preceding twelve months, the estimated annual prevalence rate (persons) of falls was 28.0%. Standardized for age, the rate was twice as high in women as in men. Rates increased with age but more steeply in men than in women. Compared with non-fallers, fallers had been in more recent contact with their general practitioner, showed higher prevalence of problems with mobility and daily living,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
332
3
7

Year Published

1988
1988
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 699 publications
(369 citation statements)
references
References 0 publications
27
332
3
7
Order By: Relevance
“…Problems with mobility, balance and gait have been consistently identified as risk factors for falls. 18 This study, like previous studies, found considerable rates and outcomes of falls. The potential burden of illness associated with non-fall accidents warrants investigation in larger studies over a longer time frame.…”
Section: Brief Reportsupporting
confidence: 83%
“…Problems with mobility, balance and gait have been consistently identified as risk factors for falls. 18 This study, like previous studies, found considerable rates and outcomes of falls. The potential burden of illness associated with non-fall accidents warrants investigation in larger studies over a longer time frame.…”
Section: Brief Reportsupporting
confidence: 83%
“…Consistent with most findings from developed countries, in our sample, falls leading to severe fractures occurred predominantly in women 1,8,9 . This finding probably reflects both the higher rates of falls among women found in most incidence studies 10,11 and the fact that women are more likely than men to sustain fractures when they fall.…”
Section: Discussionmentioning
confidence: 92%
“…Há referência à redução desse risco (LaCroix et al, 1990;Ray et al, 1989), ao aumento (Cumming et al, 1991;Prudham & Evans, 1981) ou ausência de associação (Leipzig et al, 1999b). O possível efeito protetor dos diuréticos tiazídicos tem sido atribuído a uma redução na excreção urinária de cálcio, com conseqüente aumento da densidade ós-sea.…”
Section: Discussionunclassified